The photographic collection of the National Institute of Industry (INI): A window on twentieth-century Spanish industry - Junquera Casado, Isabel; Laruelo Rueda, Elena (Documentación de las Ciencias de la Información, 2025)
The role of the National Institute of Industry (INI) in Spanish industry during much of the 20th century and its interest in publicizing the activities of the companies in which participated, led to the creation of an audiovisual fund that is described the photographic collection on the occasion of its upcoming dissemination on the SEPI institutional website. This photographic collection is an interesting support material for the study of industrial development in Spain, by providing a follow-up story of industrial constructions, technical activities, works, machinery, institutional visits, etc., of INI companies with the photographs periodically requested by the Institute.
Keywords: National Institute of Industry; Public enterprises; Spanish industry; Photograph collection